Review on Factors Motivating the Information Seeking Behavior and Respondents in Medical Colleges: Examining User Behavior and Resource Utilization in Medical College Libraries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper the client network in a medical college library system comprises the personnel, understudies, from the perspective on purpose of the client whether he is the understudy, he needs assortment of information. The information which is very later to the client is constantly being recorded and the client needs particular administrations to keep him side by side with current turn of events. So as to boost the utilization of the asset of the library, reviews ought to be under-taken to ascertain the client’s retirement and information seeking behavior.